The Quantifiable Relationship between Monetary Policy and the Australian Property Market - Naqvi , Syed Muhammad Tafseer; Choo, Benjamin; Yan , Chen Yu; Fang , Tony Wen; Liu, Yihan (Contemporary Research in Business, Management and Economics Vol. 8, 2024)
The present study highlights about quantifiable relationship between Monetary Policy and the Australian Property Market. The use of monetary policy has important implications within an economy as it directly affects the supply and demand of cash itself. The adjustment of the official cash rate (OCR) and its implications on the domestic and international arenas are among Australia's most prominent uses of monetary policy. To quantify the impact of the OCR on the Australian housing markets, we look at both effects from domestic sources and effects from overseas investors. This research also draws attention to the variation in the growth rate of property prices in major Australian cities and how it reacts to the changes in this major economic variable. Our study also addresses the limitations of the devised models however, at a high level these models give guidance to general movements in housing prices given monetary policy changes with fixed money supply as determined by the Reserve Bank of Australia (RBA) and with that reinforced by movements in several macroeconomic indicators. In the case of a booming housing market where foreign direct investment and domestic real estate investment are growing rapidly, change in the adverse direction on a normal notion will not translate as anticipation based on investment expectation that leads to inaccuracy in measuring the opportunity cost of investment. We conclude that the monetary policy of RBA is effective but inefficient in dealing with property prices and property prices are affected not only by the change in OCR, but also shifts due to foreign investments and economic outlook.